2021
DOI: 10.3389/fnmol.2021.741895
|View full text |Cite
|
Sign up to set email alerts
|

Distinctive Regulation of Emotional Behaviors and Fear-Related Gene Expression Responses in Two Extended Amygdala Subnuclei With Similar Molecular Profiles

Abstract: The central nucleus of the amygdala (CeA) and the lateral division of the bed nucleus of the stria terminalis (BNST) are the two major nuclei of the central extended amygdala that plays essential roles in threat processing, responsible for emotional states such as fear and anxiety. While some studies suggested functional differences between these nuclei, others showed anatomical and neurochemical similarities. Despite their complex subnuclear organization, subnuclei-specific functional impact on behavior and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…Furthermore, Walker et al ( 33 ) reported that intra-CeA injection of anti-CART neutralizing antibodies attenuated yohimbine-induced anxiety-like behavior in the LDB test during alcohol abstinence. Given the anatomical and functional similarities between CeA and BNST ( 32 ), these findings suggest that CART within the BNST may also play a crucial role in the regulation of negative emotions, such as anxiety and fear. Further electrophysiological and behavioral studies are needed to clarify the effects of CART itself, rather than CART-expressing neurons, on the excitability of LH-projecting BNST neurons and anxiety-like behavior.…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…Furthermore, Walker et al ( 33 ) reported that intra-CeA injection of anti-CART neutralizing antibodies attenuated yohimbine-induced anxiety-like behavior in the LDB test during alcohol abstinence. Given the anatomical and functional similarities between CeA and BNST ( 32 ), these findings suggest that CART within the BNST may also play a crucial role in the regulation of negative emotions, such as anxiety and fear. Further electrophysiological and behavioral studies are needed to clarify the effects of CART itself, rather than CART-expressing neurons, on the excitability of LH-projecting BNST neurons and anxiety-like behavior.…”
Section: Discussionmentioning
confidence: 95%
“…PKC-negative neurons are represented by somatostatin-or CRF-positive neurons, and it has been reported that these three cell types cover the majority of CeL neurons and regulate fear and anxiety behaviors (27)(28)(29)(30)(31). A recent study using immunostaining for PKC combined with genetic labeling for CRF or somatostatin neurons showed similar compositions of these three major cell types between the CeL and the ovBNST (32), suggesting that a similar intranuclear reciprocal inhibitory circuit that S1.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations